1968
DOI: 10.1104/pp.43.9.1443
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Levels and Seed Dormancy

Abstract: A bstract. Dormant seeds from Fraxinus species require oold-temperature after-ripening prior to germination. Earlier, we found that abscisic acid (ABA) will inhilbit germination of excised nondormant embryos and that this can be reversed with a combination of gibberellic acid and kinetin. Using Milborrow's quantitative "racemate dilution" method the ABA concentration in 3 types of Fraxinus seed and pericarp were determined. While ABA was present in all tisisues, the highest concentration was found in the seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1970
1970
2001
2001

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…A number of trends become apparent, particularly if the content of glucosides is compared before and after germination. When dormant embryos are incubated for 10 days, there is little germination, the fresh weight increase is low, and the concentration of the three glucosides does not change significantly from that of freshly excised dormant embryos.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A number of trends become apparent, particularly if the content of glucosides is compared before and after germination. When dormant embryos are incubated for 10 days, there is little germination, the fresh weight increase is low, and the concentration of the three glucosides does not change significantly from that of freshly excised dormant embryos.…”
Section: Resultsmentioning
confidence: 95%
“…Gibberellins and cytokinins allow germination and growth of dormant embryos while ABA' prevents these processes (9). The endogenous levels of the latter hormone reflect the physiological states of the embryos, lower levels being found in nondormant seeds (10).…”
mentioning
confidence: 99%
“…The concentration of ABA in the seeds and pericarp of F. americana has been shown to decrease during the course of stratification to approximately that found in the nondormant F. ornus (6). These latter results suggested the possibility of ABA metabolism during the stratification process.…”
mentioning
confidence: 79%
“…From our data one can calculate that the dormant embryos have the capacity to metabolize ABA at the rate of at least 10 ,ug/g fresh weight*day. This compares with an ABA level in dormant seed of approximately 0.2 ,ug/g fresh weight (6).…”
Section: Discussionmentioning
confidence: 99%
“…It has been implicated in such plant growth processes as senescense, ab scission of leaves, flowers, and fruits: rest and dormancy of seeds, buds, and tubers; and inhibition of vegetative growth (Sondheimer et al, 1968;Addicott and Lyon, 1969). Addicott and Lyon (1969) showed that exogenous application of ABA can in hibit stem and bud growth.…”
Section: Auxins Have Been Implicated As Inhibitory Factors In Apical mentioning
confidence: 99%